HUBUNGAN ANTARA FAKTOR EKSTERNAL DENGAN PERILAKU TIDAK AMAN DALAM PENGOPERASIAN OVERHEAD CRANE - Fildza Fadhila (Universitas Airlangga, 2018)
Unsafe behavior is a major cause of workplace accidents. Environmental or external factor is dominant factor that can influence a behavior. The present research was conducted at PT. Bangun Sarana Baja (BSB) Gresik which is one of steel industry in construction sector. The purpose of this study was to analyze the corellation between external factor and unsafe behavior of workers in overhead crane operation at PT. Bangun Sarana Baja Gresik. This research was an observational analytic and used cross-sectional design. Population in this research was all of workshop worker that operates overhead crane (OHC) at PT. Bangun Sarana Baja (BSB) Gresik. The samples were 80 people, taken randomly by simple random sampling method. Data which had obtained then was analyzed statistically using correlation of contingency. The results showed that between variables of external factor more of them has a correlation with unsafe behavior in overhead crane operation. They are supervision (p = 0.004) and training (p = 0.000). The result of this study can be concluded that rather good supervision and unparticipated training by workers can influence their unsafe behavior. So if the value of the both variables improved to be better then it will be able to decrease the unsafe behavior in overhead crane operation.Keywords: external factor, overhead crane, unsafe behavior